2020
DOI: 10.1152/ajpendo.00298.2020
|View full text |Cite
|
Sign up to set email alerts
|

Can phytotherapy with polyphenols serve as a powerful approach for the prevention and therapy tool of novel coronavirus disease 2019 (COVID-19)?

Abstract: Much more serious than the previous severe acute respiratory syndrome (SARS) coronavirus (CoV) outbreaks, the novel SARS-CoV-2 infection has spread speedily, affecting 213 countries and causing ~17,300,000 million cases and ~672,000 (~+1500/day) deaths globally (as of July 31th, 2020). The potentially fatal COVID-19, caused by air droplets and airborne as the main transmission modes, clearly induces a spectrum of respiratory clinical manifestations, but it also affects the immune, gastrointestinal, hematologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 251 publications
0
61
0
1
Order By: Relevance
“…General, nonspecific therapies such as strengthened supportive treatment, vitamin-D administration, adequate energy intake, evaluation of water and electrolyte balance, and effective oxygen therapy measures are also important to be administered promptly by the general practitioner and home-based medical care staff. 110,111 Early administration of antithrombotic agents such as low-molecular-weight heparin (LMWH), direct orally active factor Xa inhibitors (apixaban, rivaroxaban), or sulodexide to patients at risk of disease worsening reduces the risk of hospitalization, need for oxygen support, or even mortality. [112][113][114][115][116][117] Nevertheless, particularly for LMWHs, the optimal dose needs to be thoroughly evaluated.…”
Section: Prevention Detection Anticipationmentioning
confidence: 99%
“…General, nonspecific therapies such as strengthened supportive treatment, vitamin-D administration, adequate energy intake, evaluation of water and electrolyte balance, and effective oxygen therapy measures are also important to be administered promptly by the general practitioner and home-based medical care staff. 110,111 Early administration of antithrombotic agents such as low-molecular-weight heparin (LMWH), direct orally active factor Xa inhibitors (apixaban, rivaroxaban), or sulodexide to patients at risk of disease worsening reduces the risk of hospitalization, need for oxygen support, or even mortality. [112][113][114][115][116][117] Nevertheless, particularly for LMWHs, the optimal dose needs to be thoroughly evaluated.…”
Section: Prevention Detection Anticipationmentioning
confidence: 99%
“…We have previously shown the neuroprotective potential of naringenin through modulation of inflammatory mediators (NF-κB, TNF-α, IL-1β, etc) and microglia activation in the CNS ( Nouri et al, 2019 ), thereby it could mitigate the neuronal signs of COVID-19 mediated by the inflammatory mediators. As another phenolic compound, resveratrol has shown promising beneficial effects against COVID-19, through the activation of ERK1/2 and SIR1 signaling pathways related to survival, DNA protection ( Levy et al, 2020 ; Ma and Li, 2020 ), and anti-neuroinflammatory responses ( Bastianetto et al, 2015 ). It also inhibits neuroapoptosis by reducing FGF-2 and suppressing NF-κB ( Xu et al, 2018 ).…”
Section: Potential Of Phytochemicals Against Covid-19 Neurological Asmentioning
confidence: 99%
“…Polyphenols are a cluster of natural compounds with promising results. Recently, it is reported that phototherapy with polyphenols serves as a powerful approach for the prevention and therapy tool of novel coronavirus disease 2019 (COVID-19) (Levy, Delvin, Marcil, & Spahis, 2020).…”
Section: Polyphenols As Antiviral Agentsmentioning
confidence: 99%